In what ways Enterprise Rent-a-Car’s CSR activities jointly serve the company's strategic motives and the interests of the society? - Gupta, Kaanan (2011)
This study provides an exploratory investigation of the link between Corporate Social Responsibility (CSR) and Firm’s Competitive Advantage concurrently contributing to our understanding of how organizations impact society and potentially benefit a variety of stakeholders (Ray, 2006). The impact that an organization’s corporate social responsibility (CSR) has on their current and potential employees, customers and the society can be crucial to organizational survival (Ibid.). This study, therefore, poses three primary research questions (1) Does CSR lead to improved financial performance or gain of any valuable and rare resources?, (2) What kind of benefits does CSR have that can lead to improved financial performance (Branco and Rodrigues, 2006)? and (3) How does the firm’s approach to stakeholder management influence its ability to protect and enhance the value of these resources? Corporate Social Reputation, the perception of the firm by its internal and external stakeholders, is argued to be a valuable and a rare resource that CSR provides. By building positive stakeholder relationships through CSR the firm is able to positively influence stakeholder assessment and gain ‘reputational capital’. The value of reputational capital lies in its ability to promote operational efficiency and beget service differentiation, which independently as well as in tandem, grant firms superior performance over their competitors (Peters, 2007: 3).